JuSpace: A tool for spatial correlation analyses of magnetic resonance imaging data with nuclear imaging derived neurotransmitter maps - Dukart, Juergen; Holiga, Stefan; Rullmann, Michael; Lanzenberger, Rupert; Hawkins, Peter C T; Mehta, Mitul A; Hesse, Swen; Barthel, Henryk; Sabri, Osama; Jech, Robert; Eickhoff, Simon B (Human brain mapping, 2021)
Recent studies have shown that drug-induced spatial alteration patterns in resting state functional activity as measured using magnetic resonance imaging (rsfMRI) are associated with the distribution of specific receptor systems targeted by respective compounds. Based on this approach, we introduce a toolbox (JuSpace) allowing for cross-modal correlation of MRI-based measures with nuclear imaging derived estimates covering various neurotransmitter systems including dopaminergic, serotonergic, noradrenergic, and GABAergic (gamma-aminobutric acid) neurotransmission. We apply JuSpace to two datasets covering Parkinson's disease patients (PD) and risperidone-induced changes in rsfMRI and cerebral blood flow (CBF). Consistently with the predominant neurodegeneration of dopaminergic and serotonergic system in PD, we find significant spatial associations between rsfMRI activity alterations in PD and dopaminergic (D2) and serotonergic systems (5-HT1b). Risperidone induced CBF alterations were correlated with its main targets in serotonergic and dopaminergic systems. JuSpace provides a biologically meaningful framework for linking neuroimaging to underlying neurotransmitter information.
Keywords: Synaptic Transmission; Cerebrovascular Circulation; Tomography, Emission-Computed, Single-Photon; magnetická rezonanční tomografie; neuroimaging; mozkový krevní oběh; jednofotonová emisní výpočetní tomografie; Positron-Emission Tomography; pozitronová emisní tomografie; neurotransmiterové látky; Receptors, Neurotransmitter; Parkinson's disease; positron emission tomography; Neuroimaging; nervový přenos; neurozobrazování; Neurotransmitter Agents; neuropharmacology; receptory neurotransmiterů; lidé; Humans; magnetic resonance imaging; neurotransmission; Magnetic Resonance Imaging; Parkinson Disease; Parkinsonova nemoc